Myo-inositol improves the viability of boar sperm during liquid storage - Jawad, Ali; Oh, Dongjin; Choi, Hyerin; Kim, Mirae; Cai, Lian; Lee, Joohyeong; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2023)
Introduction Liquid preservation of boar semen is a highly preferred method for semen preservation in pig production. However, oxidative stress in liquid preservation of stored boar semen in poses a significant time dependent challenge in. However, oxidative stress is the main challenge during the liquid preservation of boar semen in a time dependent manner. Therefore, supplementation of sperm with antioxidants during storage to protect them from oxidative stress has been the focus of recent research. Myo-inositol (Myo-Ins), the most active form of inositol, which belongs to the vitamin (Vit.) B1 group has been shown to improve semen quality(add reference)(1). This study aimed to investigate whether Myo-Ins supplementation protects boar sperm in liquid preservation against oxidative Formatted: Not Highlight Formatted: Not Highlight 2 This is a provisional file, not the final typeset article stress and determine the appropriate concentration of Myo-Ins to be used in this regard. Methods: Boar sperm was diluted with a semen extender with different concentrations of Myo-Ins (2, 4, 6, and 8 mg/mL) depending on the previous studies(1, 2). Sperm motility and viability, plasma membrane and acrosome integrity, mitochondrial membrane potential (MMP), semen time survival, and gene expression were measured and analyzed on days 0, 1, 3, 5, and 7 for the different samples. Results: Different concentrations of Myo-Ins exerted different protective effects on the boar sperm quality. The addition of 2 mg/mL Myo-Ins resulted in higher sperm motility and viability, plasma membrane and acrosome integrity, MMP, and effective survival time. Investigation of mRNA expression patterns via qRT-PCR suggested that the 2 mg/mL Myo-Ins sample had increased expression of antioxidative genes. Discussion: Conclusion: The addition of Myo-Ins to semen extender improved the boar semen quality by decreasing the effects of oxidative stress during liquid preservation at 17 °C. Additionally, 2 mg/mL is the optimum inclusion concentration of Myo-Ins for semen preservation.